2020
DOI: 10.3390/polym12102232
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicological Testing and Thermal Decomposition of Drive and Transport Belts Made of Thermoplastic Multilayer Polymer Materials

Abstract: The article presents the potential impact of flat drive and transport belts on people’s safety during a fire. The analysis distinguished belts made of classically used fabric–rubber composite materials reinforced with cord and currently used multilayer polymer composites. Moreover, the products’ multilayers during the thermal decomposition and combustion can be a source of emissions for unpredictable and toxic substances with different concentrations and compositions. In the evaluation of the compared belts, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 50 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…This dependence was developed on the basis of the experimental tests of V-belts and flat belts. The results show that flat drive belts have less toxic properties under fire conditions than V-belts, mainly due to the kinds of materials, such as PA or NBR, with which the flat belts were made 10 , 32 . In paper 32 , the influence of various polymers, e.g., polyamide and polyurethane, on toxicity emissions was described.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This dependence was developed on the basis of the experimental tests of V-belts and flat belts. The results show that flat drive belts have less toxic properties under fire conditions than V-belts, mainly due to the kinds of materials, such as PA or NBR, with which the flat belts were made 10 , 32 . In paper 32 , the influence of various polymers, e.g., polyamide and polyurethane, on toxicity emissions was described.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that flat drive belts have less toxic properties under fire conditions than V-belts, mainly due to the kinds of materials, such as PA or NBR, with which the flat belts were made 10 , 32 . In paper 32 , the influence of various polymers, e.g., polyamide and polyurethane, on toxicity emissions was described. In the flat belt case, the dominant compounds released during combustion are CO and CO 2 (all burned belts), as well as HCN, SO 2 and HBr.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The belts used in tension transmissions are most often made of polymeric materials or their composites [ 1 , 2 , 3 ]. As a rule, styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), ethylene propylene diene monomer (EPDM) and natural rubber (NR) are used for drive belts, as well as classic thermoplastics, i.e., polyamide (PA), polyvinylidene dichloride (PVDC), acrylonitrile butadiene styrene (ABS), polyurethane (PU), polyethylene (HDPE), polypropylene (PP), polyoxymethylene (POM) [ 2 , 4 ]. However, when higher strength, thermal and chemical resistance and higher flammability are required from the belts, then polymer composites filled with glass fibers (Nylon 6.6 with glass fiber), carbon fiber (carbon fiber) or poly(lactic acid) PLA-carbon are used.…”
Section: Introductionmentioning
confidence: 99%
“…Franco-Urquiza et al [ 34 ] performed the thermogravimetric analysis at 5, 10 and 20 °C/min allowed determining the degradation kinetic parameters based on the Friedman and Kissinger models for neat polyester and nanocomposites, which showed that heating rates promoted an increase in the temperature degradation. Krawiec et al [ 35 ] used a testing methodology to determine the toxicometric indicators on belts made of classically used fabric–rubber composite material, and evaluated the degradation kinetics of the polymeric belts by (TGA). Zhang et al [ 36 ] investigated the effect of basalt fiber content in HDPE matrix composites on the thermal decomposition process using dynamic thermogravimetric analysis and utilized improved Coats–Redfern (C-R), Flynn–Wall–Ozawa (F-W-O), Friedman and Kissinger methods to ascertain the specific apparent activation energy (E a ) of each component and composite material.…”
Section: Introductionmentioning
confidence: 99%